Clinico pathological study of thyroid lesions in a rural tertiary care centre - Dr Sheela Lakshman rao Gaikwad; Dr. Santosh Baliram Bhokare; Dr.Vaibhav Vilas Deshmukh; Dr Mona Dhillon; Dr Shivkanya Marotrao Kale (Tropical Journal of Pathology and Microbiology, 2018)
Objective: Present study is clinicopathological study of thyroid lesions in a rural tertiary care Centre. Thyroid lesions are fairly common worldwide and are commonly encountered in clinical practice in rural areas also.It causes more concern because of high probability of malignancy in solitary thyroid nodules.Materials and Methods: Prospective study done in Dept. of pathology over a period of 6 months in a rural tertiary care centre. It included clinical examination, routine investigations and histopathological diagnosis.Result: In our study of 40 cases, 31 were diagnosed as non-neoplastic and 9 as neoplastic. Most common clinical presentation was midline neck swelling, commonly on right side and majority of patients were diagnosed with colloid goitre (62.5%) followed by multinodular goitre (20%) on ultrasonography. The non-neoplastic to neoplastic ratio of 3.4:1.with female to male ratio of 19:1. Colloid goitre was the most common non neoplastic lesion and follicular adenoma was the most common neoplastic lesion.Conclusion: In current study conducted in a rural tertiary care centre, thyroid lesions were common in age group of 3rd to 5th decade with female predominance. Benign lesions were common than neoplastic lesions. Histopathological diagnosis of thyroid lesions is important for early diagnosis and treatment of neoplastic lesions.